Effect of Temporal Organization of the Visuo-Locomotor Coupling on the Predictive Steering - Rybarczyk, Yves P. (Frontiers in Psychology, 2012)
Studies on the direction of a driver’s gaze while taking a bend show that the individual looks toward the tangent-point of the inside curve. Mathematically, the direction of this point in relation to the car enables the driver to predict the curvature of the road. In the same way, when a person walking in the street turns a corner, his/her gaze anticipates the rotation of the body. A current explanation for the visuo-motor anticipation over the locomotion would be that the brain, involved in a steering behavior, executes an internal model of the trajectory that anticipates the completion of the path, and not the contrary. This paper proposes to test this hypothesis by studying the effect of an artificial manipulation of the visuo-locomotor coupling on the trajectory prediction. In this experiment, subjects remotely control a mobile robot with a pan-tilt camera. This experimental paradigm is chosen to manipulate in an easy and precise way the temporal organization of the visuo-locomotor coupling. The results show that only the visuo-locomotor coupling organized from the visual sensor to the locomotor organs enables (i) a significant smoothness of the trajectory and (ii) a velocity-curvature relationship that follows the “2/3 Power Law.” These findings are consistent with the theory of an anticipatory construction of an internal model of the trajectory. This mental representation used by the brain as a forward prediction of the formation of the path seems conditioned by the motor program. The overall results are discussed in terms of the sensorimotor scheme bases of the predictive coding.